SOME ISSUES OF INVOLVEMENT IN THE REALIZATION OF THE GOALS PURSUED BY A GROUP WITH A CRIMINAL SUBCULTURE - Babakhanyan, Arman (State and Law, 2022)
The article is devoted to some issues of involvement in the realization of the goals pursued by a group with a criminal subculture. In particular, the author of the article discussed the lack of need to provide a special norm excluding criminal liability for the above-mentioned act, when the participation of a person, who is not a member of such a group, with any role in the realization of the group’s goals was manifested by performing actions considered permissible by the legislation. In addition, reference was made to the need to provide a separate article for the responsibility for the act under discussion, to establish a special incentive norm exempting the persons who committed the crime and demonstrated positive post-criminal behavior from criminal liability. As a result, the author proposed to provide responsibility for the above-mentioned crime in a separate article and establish more lenient punishment, as well as provide a special incentive norm exempting from criminal responsibility for the persons involved in the realization of the goals pursued by such a group, if the latter contributed to the disruption of the group’s activities.